Imagestream detection and characterisation of circulating tumour cells – A liquid biopsy for hepatocellular carcinoma? - Ogle, Laura F.; Orr, James G.; Willoughby, Catherine E.; Hutton, Claire; McPherson, Stuart; Plummer, Ruth; Boddy, Alan V.; Curtin, Nicola J.; Jamieson, David; Reeves, Helen L. (Journal of hepatology, 2016)
[Display omitted] The lack of progress in developing and delivering new therapies for hepatocellular carcinoma (HCC) is in part attributed to the risk related avoidance of tumour biopsy at diagnosis. Circulating tumour cells (CTCs) are a potential source of tumour tissue that could aid biological or biomarker research, treatment stratification and monitoring. An imaging flow cytometry method, using immunofluorescence of cytokeratin, EpCAM, AFP, glypican-3 and DNA-PK together with analysis of size, morphology and DNA content, for detection of HCC CTCs was developed and applied to 69 patient and 31 control samples. The presence of CTCs as a prognostic indicator was assessed in multivariate analyses encompassing recognised prognostic parameters. Between 1 and 1642 CTCs were detected in blood samples from 45/69 HCC patients compared to 0/31 controls. CTCs positive for the epithelial markers cytokeratin and EpCAM were detected in 29% and 18% of patients respectively, while an additional 28% of patients had CTCs negative for all markers other than size and evidence of hyperploidy. CTC number correlated significantly with tumour size and portal vein thrombosis (PVT). The median survival of patients with >1 CTC was 7.5months versus >34months for patients with <1 CTC (p<0.001, log-rank), with significance retained in a multivariate analysis (HR 2.34, 95% CI 1.005–5.425, p=0.049) including tumour size and PVT. The use of multiple parameters enhanced HCC CTC detection sensitivity, revealing biological associations and predictive biomarker potential that may be able to guide stratified medicine decisions and future research. Characteristics of tumour tissues can be used to predict outcomes for individual patients with cancer, as well as help to choose their best treatment. Biopsy of liver cancers carries risks, however, and is usually avoided. Some cancer cells enter the blood, and although they are very rare, we have developed a method of finding and characterising them in patients with liver cancer, which we hope will provide a low risk means of guiding treatment.